The night we became strangers - Hughes, Lorena (Kensington Publishing Corporation, 2025)
1957: Aspiring photojournalist Valeria Anzures returns to her hometown of Quito with a secret: to discover what really happened to her parents. The disastrous 1949 War of the Worlds show caused a mob to torch her family's radio station-and the newspaper run by their closest friends, the Monteros. The tragedy shattered the families' relationship-and left the station on precarious financial ground. Now, expected to save her family's legacy through an arranged marriage, Valeria will risk everything to find out the truth. Even if it means allying with the man she's always loved-but who now treats her like a stranger. For Matias Montero, the scars of that night run deep. He saved his mother but blames himself for not rescuing his father. As a journalist, he feels Valeria is a rival. Still, they're both on the same mission. Perhaps, together, they can unearth the past their families and friends would rather remain buried. Valeria and Matias soon find trusting each other is as dangerous as the attraction they can't resist. Between their families' mutual hatred, duplicitous witnesses, and insidious lies, exposing the real story will put their future on the line-and ignite revelations no one saw coming.